Factors that impact on talent development within a talent detection program - Morley, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Talent detection is a form of talent identification that identifies athletes from outside the sport of interest as distinct from talent selection which selects athletes from within the sport (Vaeyens et al., 2008). Systematic talent detection and development (TDD) programs have become increasingly prevalent in recent years however their viability has not been well established in the literature. Therefore, the aim of this study was to examine the characteristics of a successful TDD program and to investigate why some talent detection athletes transition successfully into high performance sport, while others do not. Methods: A case study approach was adopted using talent detected flatwater kayakers. Athletes were matched in pairs with the key differentiating factor being their highest level of achievement in kayaking with one athlete reaching Australian team representation and the other unable to reach this benchmark. Athletes (n=14) and their coaches (n=4) participated in semi-structured interviews and completed questionnaires based on Gagne`s (2009) Differentiated Model of Giftedness and Talent. Additionally, on water and off water performance data was collected prospectively and analysed. Results: Coaches, successful athletes and underachieving athletes raised a variety of contrasting explanations for performance. Coaches emphasised the importance of athletes` natural ability, intrapersonal characteristics including determination and `coachability`, and environmental and process factors such as the importance of early and ongoing success and a satisfying social setting. Successful athletes attributed their achievements to environmental provisions such as quality training programs and international competition, influential others including parents and coaches, and intrapersonal factors such as motivation and perseverance. The impact of poor injury management, competing priorities, performance plateaus, and ambiguous expectations were highlighted as consequential by underachieving athletes. Discussion: Factors found to facilitate and constrain successful athlete development within a TDD setting will be presented. Discussion will focus on theoretical insights gained and recommendations for improving current TDD practices and maximising athlete retention.